Uji Fitokimia Dan Aktivitas Antioksidan Ekstrak Etanol Daun Kelor (Moringa Oleifera) - Sudirman, Sudirman; Sulfiani, Sulfiani; Mainassy, Meillisa Carlen; Pramono, Edi (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Free radicals play a major role in causing damage to cells and body tissues, which can trigger various degenerative diseases. One preventive strategy is the use of antioxidants. Moringa oleifera leaves are a herb known to be rich in phytochemical compounds with high antioxidant potential. Objective: This study aimed to evaluate the phytochemical content and antioxidant activity of ethanol extract of Moringa leaves as a natural ingredient with potential use in the development of pharmaceutical products or functional foods. Methods: Moringa leaves were extracted using a maceration method with 96% ethanol as a solvent. Phytochemical tests were conducted to identify secondary metabolites such as alkaloids, flavonoids, saponins, tannins, steroids, and terpenoids. Antioxidant activity was analyzed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, and IC₅₀ values were calculated to determine their antioxidant potential. Results: The ethanol extract of Moringa leaves contained flavonoids, saponins, tannins, and alkaloids. The DPPH test results showed that the extract had an IC₅₀ value of 65.4 µg/mL, which is categorized as moderate antioxidant activity. Conclusion: The ethanol extract of Moringa leaves contains diverse phytochemicals and significant antioxidant activity. This demonstrates the great potential of Moringa leaves as a source of natural antioxidants in the development of herbal medicines and functional food products.